Optimalisasi Penggunaan Heat Input pada Pengelasan Pipa Spiral Untuk Meningkatkan Kekuatan Sambungan - Subeki, Nur (Jurnal Teknik Industri, 2009)
Submerged Arc Welding is a welding process used for  fabrication of pipes, for example spiral welded pipes. The technique can be operated automatically and has a high reliability in many various welding aplication. Some factor affecting the strength of weld metals are heat input, current, chemical composition of filler and flux, welding speed and cooling rate. The purpose of this thes is is to obtaine microstructure containing acicular ferrite which give high strength and low hardness of the submerged arc welded pipes.Material used in this experiment was API 5L X-52 spiral welded steel pipes, Welding was carried out using voltage of 35 volt, welding speed of 13,67 mm/s whereas heat input was varied, namely 2,059 kJ/mm, 2,123 kJ/ mm, 2,187 kJ/mm, 2,252 kJ/mm and 2,316 kJ/mm. A series of mechanical  properties test were carried out including hardness and tensile test. The result show that, an increase in weld heat input make increased the tensile strength but the hardness number  decrease.